Reflection on the future of std approach towards the technological progress - Duarte, Geraldo (Brazilian Journal of Sexually Transmitted Diseases, 2012)
One of the biggest challenges to practice contemporary medi-cine is the continuous adaptation to the health financing mo-dels, often forcing us a dangerous detachment of the Hipocratic principles that rule our activities in the patient’s care. The result of this equation is a glaring duality between the quality care exercise and the conditions to accomplish it. [...]